Biomass converted carbon quantum dots for all-weather solar cells. (10th December 2017) - Meng, Yuanyuan; Zhang, Yue; Sun, Weiyin; Wang, Min; He, Benlin; Chen, Haiyan; Tang, Qunwei
Graphical abstract: Highlights: CQDs are converted from soybean powders by a hydrothermal method. The biomass converted CQDs are used for all-weather DSSCs. The so-called all-weather DSSCs can generate electricity in the daytime and dark. A dark efficiency as high as 7.97% is determined on the all-weather photovoltaics. The launched solar cell extend our knowledge of advanced all-weather solar cells. Abstract: A great challenge for state-of-the-art photovoltaic devices is to realize electric power generation in all weathers. We constructively demonstrate here the conversion from biomass to carbon quantum dots for all-weather carbon quantum dot solar cells that can generate electricity in the daytime and in the dark. The combination of green-emitting long persistence phosphors with mesoscopic titanium dioxide realizes optical storage by composite photoanode under illumination and excitation to monochromatic green light in the dark. The optimized all-weather solar cell yields maximized dark power conversion efficiency as high as 7.97% along with persistent electricity output for several hours. This work begins a photovoltaic revolution to forward all-weather solar cells as future energy solutions.